The influence of hydration on the architectural rearrangement of normal and neoplastic human breast tissues. Issue 2 (February 2019) - Conceição, A.L.C.; Meehan, K.; Antoniassi, M.; Piacenti-Silva, M.; Poletti, M.E.
Abstract: In adult women, the water-content represents between 50% and 70% of the mass in normal breast tissues and this percentage is increased within diseased tissues. Water molecules play an essential role in the structural organization of biological tissues such as breast. Then, in this study, we have investigated the influence of the water molecules on the breast tissue organization and their role on the hierarchical tissue rearrangement promoted by tumor growth. SAXS and WAXS techniques were used to analyze healthy, benign and malignant human breast samples in native and lyophilized conditions. The scattering profiles in SAXS and WAXS regime of each tissue type in both conditions were compared in order to identify the structural transformation in these tissues and verify the water influence on the morphological arrangement of normal and pathological human breast tissues. From SAXS, changes at the axial periodicity of collagen fibrils were revealed. Additionally, when the water content has removed a peak at q = 4.17 nm −1 (that was present only in pathological samples) shifted in opposite directions within benign and malignant lesions. From WAXS, water and fatty acids were identified within native samples. However, after freeze-drying, only the fat component was observed in the scattering profiles. Therefore, when the water molecules were removed from the samples, structural changes associated with pathological progression were visible. From this, insights about their influence over the changes promoted by the tumor growth have been proposed. Finally, the findings of this study have the potential to provide valuable information to the development of new target therapy.